Tensile properties of alkali treated sugar palm fiber - Mohamad Nazirul Mubin, Merzuki (2013)
A study of the effect of alkaline treatment on the tensile properties of sugar palm fiber.The fiber were treated using sodium hydroxide (NaOH) with 2%, 4% and 6% concentration solution for 1 hour soaking time. The purpose of treating fiber with alkali was to enhance the tensile strength and young modulus of single sugar palm fiber. The maximum tensile strength for untreated fiber is 63.05 MPa.The maximum tensile strength for occurred at 2% NaOH solution with 1 hour of soaking time, i.e 67.85 MPa. But, the maximum fiber for treated 4% NaOH solution with 1 hour of soaking time is 76.37MPa and for fiber treated 6% NaOH solution is 82.13 MPa.